(untitled) (Docentes 2.0 Journal, 2024)
Information and Communication Technologies (ICT), including mobile applications, have transformed how people carry out their daily activities due to their presence in all aspects of daily life. The research objective was to determine the relationship between technological appropriation and the use of mobile applications by primary school teachers. It was carried out under a positivist paradigm, using a hypothetical-deductive method, with a quantitative approach and a non-experimental, correlational, and cross-sectional design. The population consisted of 41 primary school teachers from a school in Majes, Arequipa, and the sample was intentionally selected using a census. The technique used was the survey, and two questionnaires validated by expert judgment and with high reliability were used. The results showed a greater tendency at a regular level for technological appropriation and a moderate level for the use of mobile applications, also corroborating a significant relationship between the variables with an acceptable intensity (Rho = 0.472). Knowledge of computing, use of technology, interest, improved results, perception of technological benefit and development of inventive capacity facilitated pedagogical use, usefulness in teaching work, use of internal and external agents in the institution, need for guidance and support, and intention to use technology for educational purposes. In this sense, the greater the technological appropriation, the greater the frequency with which teachers use mobile applications.